QUANTITATIVE EVALUATION OF FACTORS INFLUENCING PAVEMENT DESIGN LIFE USING COMPUTER PROGRAM DAMA - Tulus Pribadi, Lucky
QUANTITATIVE EVALUATION OF FACTORS INFLUENCING PAVEMENT DESIGN LIFE USING COMPUTER PROGRAM DAMA, Pribadi, Lucky T. 1988, Program Sistem dan Teknik Jalan Raya, Fakultas Pasca Sarjana, Institut Teknologi Bandung. The performance of highway pavements is largely a function of the accuracy of assumptions made at the design stage and of the level of variability introduced during production and installation of the pavement materials. Empirical methods of pavement design inherently take into account construction variability but do not permit isolation and quantification of the effect of variability in individual parameters. Extrapolation of design assumptions to other situations is difficult and of questionable accuracy. Analytical methods of pavement design provide the engineer with the capability to make quantitative judgements as to the significance of the wide range of parameters that influence pavement structural design and performance. The most recent thickness design charts produced by the Asphalt Institute were derived from structural analysis and are based on consideration of two primary modes of flexible pavement deterioration: cracking of the asphalt layer and rutting in the wheel-track. As an alternative to the design charts, the microcomputer-based design package, DAMA, may be used for extensive evaluation of site-specific factors that can influence design. m The investigation described in this thesis used the computer program DAMA to evaluate the variability that may be introduced at three stages of design and construction processes. Such a variability can result from assumptions made at the design stage, quality control during production of pavement materials, and quality control of the construction process. A flexible pavement design proposed for the Padalarang-Cileunyi toll road was adopted as the control pavement. Factors considered in the analysis included the thickness and quality of the unbound granular layer, height and quality of embankment materials, quality of the soil supporting the embankment, environmental factors, bitumen mix characteristics, and thickness of the bituminous layer. The results of the investigation indicated that the computer program DANA can be a valuable aid to the decision making process that leads to the selection of an optimum pavement desig